2006
DOI: 10.1007/s00125-005-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conjugated equine oestrogen on diabetes incidence: the Women’s Health Initiative randomised trial

Abstract: Postmenopausal therapy with oestrogen alone may reduce the incidence of treated diabetes. The effect is smaller than that seen with oestrogen plus progestin. CEO should not, however, be used with the intention of preventing diabetes, as its well-described adverse effects preclude long-term use for primary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
4
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(126 citation statements)
references
References 36 publications
(40 reference statements)
4
115
4
3
Order By: Relevance
“…Another possibility is that a shift towards android obesity in women indicates a change in hormonal state as is observed in post-menopausal women and in women with polycystic ovarian syndrome or Turner's syndrome, which can elevate type 2 diabetes risk. Oestrogen replacement among post-menopausal women is associated with a lower incidence of type 2 diabetes [28,29]. The reason for the interaction with sex with regard to hip circumference is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that a shift towards android obesity in women indicates a change in hormonal state as is observed in post-menopausal women and in women with polycystic ovarian syndrome or Turner's syndrome, which can elevate type 2 diabetes risk. Oestrogen replacement among post-menopausal women is associated with a lower incidence of type 2 diabetes [28,29]. The reason for the interaction with sex with regard to hip circumference is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…A decreased peripheral blood flow may limit insulin delivery and promote insulin resistance. Results of the WHI trial suggested that a decrease in insulin resistance, induced by the MHT, may have been responsible for the lower incidence of diabetes observed in the women who received the active treatment [13,14]; these results were confirmed in a meta-analysis [15]. As in a recent study [36], the relationship was no longer significant after discontinuation of MHT use, when the model was adjusted for BMI during follow-up.…”
Section: Discussionmentioning
confidence: 73%
“…Though our study is the first to consider the effect of different types of MHT combination on diabetes risk, several authors have reported the impact of different types of hormone therapy on intermediate risk factors. In the WHI trial, conjugated equine oestrogen combined with MPA was found to improve insulin sensitivity [14]. Low-dose dydrogesterone associated with oestradiol may lead to a decrease in the concentration of circulating insulin [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations